The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1021/acsami.6b08589
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure and Surface Properties of CoxZn1–xO Thin Films for Ozone Gas Sensing

Abstract: A detailed study of the structural, surface, and gas-sensing properties of nanostructured CoZnO films is presented. X-ray diffraction (XRD) analysis revealed a decrease in the crystallization degree with increasing Co content. The X-ray absorption near-edge structure (XANES) and X-ray photoelectron spectroscopies (XPS) revealed that the Co ions preferentially occupied the Zn sites and that the oxygen vacancy concentration increased as the amount of cobalt increased. Electrical measurements showed that the Co d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 45 publications
0
60
0
Order By: Relevance
“…Additionally, Figure 1b We observed that the heterojunction exhibited a good sensor response even for the lowest O3 level (20 ppb), and also a total reversibility, and good repeatability. It is important to remember that ozone levels higher than 100 ppb are known to be harmful to human health [6]. To evaluate the selectivity, the heterojunction was exposed to oxidizing (NO2) and reducing gases (NH3, and CO).…”
Section: Characterization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Figure 1b We observed that the heterojunction exhibited a good sensor response even for the lowest O3 level (20 ppb), and also a total reversibility, and good repeatability. It is important to remember that ozone levels higher than 100 ppb are known to be harmful to human health [6]. To evaluate the selectivity, the heterojunction was exposed to oxidizing (NO2) and reducing gases (NH3, and CO).…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Among the MOS, zinc oxide (ZnO) and tin oxide (SnO2) are n-type wide band-gap semiconductors (Eg = 3.2 and 3.6 eV, at 300 K) [4,5]. These compounds have attracted much interest due to their wide range of applications, mainly as chemoresistors [1,6]. The traditional semiconductor gas sensors (e.g., ZnO, WO3, SnO2, and In2O3) have generally found application for use at temperatures >200 °C, hindering the monitoring of gas composition in an environment containing explosive species since high temperature could trigger an explosion [7].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 and Ti 1− x Nb x O 2 ( x = 3 mol.%) powders were synthesized by the polymeric precursor method. This methodology has been widely used for preparation of several polycation oxides in the form of nanostructured films and ceramic powders . The main advantages of this route are the high degree of control over the composition, and easy reproducibility .…”
Section: Methodsmentioning
confidence: 99%
“…This methodology has been widely used for preparation of several polycation oxides in the form of nanostructured films and ceramic powders . The main advantages of this route are the high degree of control over the composition, and easy reproducibility . Titanium isopropoxide (IV) (Ti[OCH (CH 3 ) 2 ] 4 –Alfa Aesar) and niobium ammonium oxalate (NH 4 H 2 [NbO–(C 2 O 4 ) 3 ] 3H 2 O − CBMM company, Araxá‐MG, Brazil) were used as precursor materials.…”
Section: Methodsmentioning
confidence: 99%
“…The naturally present ozone (O3) in the atmosphere is harmful even at low concentrations (<200 ppb). It leads to health problems such as inflammation or respiratory tract [4]. It well known that Metal Oxide Semiconductor (MOX) sensors require high operating temperature (>200 °C ) to accelerate molecule chemical reactivity in the adsorption and desorption process.…”
Section: Introductionmentioning
confidence: 99%